2016
DOI: 10.3892/mmr.2016.5125
|View full text |Cite
|
Sign up to set email alerts
|

16α, 17α-epoxypregnenolone-20-oxime inhibits NO and IL-6 production in LPS-treated RAW264.7 cells

Abstract: Abstract. It has previously been repor ted t hat 16α, 17α-epoxypregnenolone-20-oxime (EPREGO) exerts an inhibitory effect on nitric oxide (NO) production and inducible NO synthase (iNOS) expression in microglia. The present study aimed to investigate the effects of EPREGO on the lipopolysaccharide (LPS)-induced inflammatory response in RAW264.7 macrophage cells, and to determine the underlying molecular mechanisms using western blot analysis, enzyme-linked immunosorbent assays and fluorescence-activated cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the present study, IC/Ig was demonstrated to suppress TLR4-triggered IL-6 secretion, but not TNF-α production, in B cells. A previous study has reported that LPS-triggered IL-6 release from RAW264.7 macrophages is inhibited by 16α, 17α-epoxypregnenolone-20-oxime (EPREGO), but EPREGO does not affect TNF-α secretion (20). Therefore, it is possible that LPS may induce activation of different signaling pathways for different cytokine secretion and the signaling pathways responsible for IL-6 secretion, but for TNF-α secretion, are inhibited by IC.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, IC/Ig was demonstrated to suppress TLR4-triggered IL-6 secretion, but not TNF-α production, in B cells. A previous study has reported that LPS-triggered IL-6 release from RAW264.7 macrophages is inhibited by 16α, 17α-epoxypregnenolone-20-oxime (EPREGO), but EPREGO does not affect TNF-α secretion (20). Therefore, it is possible that LPS may induce activation of different signaling pathways for different cytokine secretion and the signaling pathways responsible for IL-6 secretion, but for TNF-α secretion, are inhibited by IC.…”
Section: Discussionmentioning
confidence: 99%
“…16α,17β-Epoxypregnenolone-20-oxime was reported to inhibit LPS-induced JNK phosphorylation, iNOS expression, and NO production in BV-2 microglial cells and RAW264.7 macrophages [ 164 , 165 ]. Likewise, the introduction of an oxime at position 12 of dehydroabietic acid, an aromatic abietane-type diterpenoid, increased its anti-proliferative and anti-inflammatory activities in pancreatic cancer Aspc-1 cells [ 166 ].…”
Section: Oximes With Non-kinase Targetsmentioning
confidence: 99%